Empowering adolescent girls and creating lifelong champions to improve immunization coverage. (30th September 2020) - Mehmood, M; Siddiqi, D A; Abdullah, S; Baig, Q; Khan, A J; Chandir, S
Abstract: Background: Despite the global imperative to 'leave no child behind', one in every 5 children remain deprived of life-saving vaccines. Low immunization coverage is in part due to the weak linkages between community and health system, inaccessibility of outsiders to closely-knit societies and low parental awareness regarding immunizations. The Kiran Sitara (Shining Stars; KS) Adolescent Health and Leadership Program (AHLP), was implemented using adolescent girls (Kiran Sitaras-KSs) as the agents of change, who by virtue of belonging to the community were able to cause a ripple effect in boosting uptake for WHO-recommended immunizations for children under 2 years of age. Our research evaluated the feasibility of the KS community mobilization and validated KS's ability to accurately identify under-immunized and zero-dose (never-vaccinated) children. Methods: AHLP was implemented in grades 8-10 of two public secondary schools in Shikarpur and Lakhi Town, Pakistan. From April-May, 2017, a door-to-door survey was conducted by KSs followed by visits of trained staff to verify the immunization statuses identified by KSs. Results: KSs (N = 45) screened 207 children and identified under-immunized and zero-dose children with an accuracy of 74% and 94% respectively. Conclusions: Our strategy of mobilizing girls from within the communities provides a promising avenue to provide immunization services in high-risk areas that cannot be penetrated through conventional mechanisms. We are actively scaling-up our sustainable solution by implementing AHLP in 250+ schools and creating a force of 100, 000+ KSs who can promote health equity today and champion the cause in their capacity as tomorrow's mothers. Key messages: The Kiran Sitara initiative via its community-centered approach leverages the force of adolescent school girls to boost demand and provide referrals for immunization in unreached geographical pockets. The Kiran Sitara initiative utilizes the power of youth engagement to identify zero-dose and under-immunized children, link them to immunization services and improve knowledge among caregivers.